2023
DOI: 10.1007/s12020-023-03443-2
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in quality of life and predictors of symptom burden in patients with hypoparathyroidism: results from a population-based survey

Abstract: Purpose To investigate the quality of life (QoL) in patients with hypoparathyroidism (hypoPT) compared to the general population and to identify sociodemographic and clinical factors that are associated with symptom burden. Methods Patients with a diagnosis of hypoPT participated in an online survey. Information regarding the survey was distributed by treating physicians or a self-help organization. Quality of life was assessed using the EORTC QLQ-C30 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…59.4% of patients with hypoPTH reported inadequate symptom control [4 ▪ ,9]. Manifestations of hypocalcemia can range from paraesthesia, muscle spasms, arrhythmia, heart failure, laryngospasm and seizures.…”
Section: Complications Of Hypoparathyroidismmentioning
confidence: 99%
See 1 more Smart Citation
“…59.4% of patients with hypoPTH reported inadequate symptom control [4 ▪ ,9]. Manifestations of hypocalcemia can range from paraesthesia, muscle spasms, arrhythmia, heart failure, laryngospasm and seizures.…”
Section: Complications Of Hypoparathyroidismmentioning
confidence: 99%
“…Three studies reported lower SF-36 scores across all domains compared with age-matched and sex-matched clinical controls [18–20]. The newer, disease-specific Hypoparathyroid Patient Questionnaire (HPQ-28) found hypoPTH patients had the highest symptom burden in loss of vitality, pain and cramps, and numbness and tingling sensations [9]. Most studies did not find an association between calcium levels and QoL, likely because blood calcium cannot be captured in real-time with symptom onset [14 ▪▪ ].…”
Section: Complications Of Hypoparathyroidismmentioning
confidence: 99%
“…If the condition persists and the PG function is not restored, the condition becomes permanent. It is well-described that permanent hypoPT is associated with reduced quality of life (5)(6)(7)(8)(9). In addition, novel studies have shown that permanent hypoPT following total thyroidectomy also might be associated with an increased risk of cardiovascular events, renal insufficiency, malignancy as well as an increased mortality (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Hypoparathyroidism (hypoPT) is a common and serious complication associated with total thyroidectomy . It is well established that hypoPT following total thyroidectomy decreases the quality of life . However, recent studies have also shown a hitherto unknown association between permanent hypoPT and cardiovascular disease, kidney disease, and malignant disease .…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 3 It is well established that hypoPT following total thyroidectomy decreases the quality of life. 4 , 5 , 6 , 7 , 8 , 9 However, recent studies have also shown a hitherto unknown association between permanent hypoPT and cardiovascular disease, kidney disease, and malignant disease. 10 , 11 Patients with permanent hypoPT even seem to have an increased mortality.…”
Section: Introductionmentioning
confidence: 99%